Letter (summary translation) - A. C.
1940-05-24 027-0012-003 SUMMARY OF LETTER FROM WENCESLAO CARRILLO. 24th May, 1940. He says that, in his desire to do some useful work, he offered his services to the A.E.U. on the outbreak of war, for any work, including manual work, in factory or workshop. He has spoken with Tanner, who promised help on 6th March, but he has no news yet. In this situation, Araquistain arranged an interview for him with Kenneth G. Grubb, Director of the Spanish-American Department of the Ministry of Information, dealing with the suitability of writing articles for the American press which would emphasise the effort the British workers were making for the Allies' victory. Mr. Grubb is said to have indicated his willingness to receive such articles, and to pay for them. Carrillo says that he neither can nor should write articles which do not correspond to facts, and it is therefore necessary for him to visit some factories, talk with the workers, and assemble such facts as it is in the workers' and the Government's interest to release. He asks whether the Trade Unions could arrange visits to factories for this purpose. He thinks he is well-fitted to do useful work in this or other directions; he is a smith, although he has not worked at the trade for several years. Moreover, he was Commissar for the War Industry for the Central Region of Spain for the last year of the war. If we could assist him to pay a few visits to war factories, besides helping him to earn a few pounds, which are very necessary, it would contribute to the Allies' victory. He concludes by apologising for repeatedly bothering you. (signed) W. Carrillo. AC. 292/946/27/12(iii)